Language use in the English classroom : the role of students' first language in grades 9 and 10 in English classrooms in Iceland - Arna Borg Snorradóttir 1990- (2014)
The main objective of this paper was to gather insight into students’ attitudes and perceptions towards language use during English instruction. What are students’ opinions about the benefit of their own and the teacher’s use of English in the classroom? When should the teacher and the students use the first language in the English classroom? These are two of the main questions explored in this paper. A study was conducted in grades 9 and 10 in an Icelandic compulsory school. A total of 121 students participated in a questionnaire, in which they were asked about language use and their opinions towards using the target language and their first language during English instruction. The findings suggest that English should be used as the predominant language of instruction and that students’ mother tongue also serves an important and facilitating role in the English classroom. This finding may impact the way second language instruction is carried out in the upper grades of compulsory schools in Iceland. Meginmarkmið rannsóknar þeirrar sem hér verður greint frá var að veita innsýn inn í viðhorf nemenda gagnvart tungumálanotkun í enskukennslu. Hvaða ávinning sjá nemendur af þeirra eigin notkun og notkun kennarans á ensku í kennslustofunni? Hvenær ætti kennarinn og nemendur að nota móðurmálið í enskukennslu? Þetta eru tvær megin rannsóknarspurningarnar sem verða skoðaðar nánar í þessari ritgerð. Framkvæmd var könnun á nemendum í 9. og 10. bekk í íslenskum grunnskóla. Spurningalisti var lagður fyrir 121 nemendur þar sem þeir voru spurðir um tungumálanotkun og viðhorf sitt gagnvart notkun markmálsins og móðurmálsins í enskukennslu. Niðurstöður könnunarinnar gefa til kynna að enska eigi að vera notuð sem aðal samskiptamálið í kennslustofunni og að móðurmál nemenda gegni einnig mikilvægu hlutverki í enskukennslu. Niðurstöður gætu haft áhrif á framkvæmd enskukennslu á unglingastigi í grunnskólum landsins.